(untitled) (Revista Apotheke, 2020)
This article presents an overview of the studies into drawing by Stephen Farthing, artist, and researcher. His studies include definitions and taxonomies of drawing developed to broaden the understanding of the drawing practice and teaching beyond the territory of the arts field. In these studies, Farthing uses drawing itself as a means of investigation. The data was collected by Zimmermann (2016) during her doctorate studies at the University of the Arts London, with the supervision of Farthing and access to his collection of drawings, publications, and interviews. Finally, the studies track the journey into drawing research by Farthing, as well as it shows the role of drawing as an interdisciplinary knowledge, a means of investigation, and an intellectual field with territories to be explored.